Prevalence of acute appendicitis in Hospital Tengku Ampuan Rahimah, Klang in 2014 / Munirah Hasan - Hasan, Munirah (2015)
The aim of this study is to determine the prevalence of acute appendicitis in HTAR, Klang in 2014. Appendicitis is a condition in which the appendix becomes swollen, inflamed, and filled with pus. Meanwhile acute appendicitis is defined as an inflammation of the inner lining of the vermiform appendix that spreads to its other parts. Diagnosis of acute appendicitis includes physical examination to assess pain, blood test, urine test, and imaging test. Treatment for appendicitis varies. In rare cases, appendicitis may get better without surgery. Treatment might involve only antibiotics and a liquid diet. In most cases, however surgery will be necessary. Appendix sample was taken out from patient’s body by appendoctomy and it was sent to histology laboratory along with request form. Next, the sample was grossed and processed in tissue processor. Then, the specimen was embedded in wax . Specimen block was trim and section using rotary microtome. The tissue section was floated on water bath and adhere to a glass slide. The section on the glass slide was stained with haematoylin and eosin stain. The slide was dried, mount and labelled. Lastly, the slide was sent to doctor for observation. Acute appendicitis is primarily a disease of frequent disorder with an estimated risk of about 60% in males and 40% in females. Delay in presentation was found to be the reason behind the higher rate of appendicitis seen in the males population. It was often thought to be the disease of the young people, with the peak incidence occuring between the ages of 11 to 30 but the incidence of acute appendicitis can affect people at any age. Appendicitis occur more frequent in developed countries than in undeveloped countries because people in developed countries such as Malaysia are taking less fiber diet. All in all, prevalance of acute appendicitis among young adults in HTAR, Klang was the highest in the age ranging 21 to 30 and most of them are Malays. The ratio of male to female patients having acute appendicitis is 1.5:1.